Syllabus of Vocational High School Based on ESP Approach - Dewi, Sri Utami (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
This study is designed as a case study and concerned on qualitative data, which reflected what actually happened in the area of case study. The Principal, the English Teachers and Students placed as the key informants. The data gained from the informants by applying in depth interview, questionnaire, documentation and observation. The data are analyzed by employing two methods, those are: descriptive qualitative and descriptive quantitative. There are two problems in this study that can be seen from two perspectives; syllabus designing and students’ needs analysis. From the perspectives of syllabus designing, the problem arise on defining a syllabus typically as the content standart which is commonly and formally provided by the higher authority (i.e. Ministry of National Education). In evidence, the existence of UN (Ujian Nasional/National Examination) makes teachers come into problems. Moreover, from learners’ needs analysis perspective, teachers define Target Situation Analysis (TSA) mainly as the content of students’ subject matters of their majors rather than students’ linguistic performance after finishing the course. Furthermore, the teachers define the Present Situation Analysis (PSA) mainly as students’ strengths/weaknesses in following the English course.